Critical thinking development by using the implicit content of songs - Arias Casas, Daniel Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This study aimed to reveal the critical thinking development process of third English level students at a Languages Institute in a public University in Colombia when using the implicit content of songs through problem-based activities. A set of problem-based activities became the mechanism to achieve the prime goal of this study. The instruments from which the data was collected were video-recordings, focus group interviews and students’ artifacts. The findings revealed three main aspects according to the purpose of the research: the teacher must set up appropriate conditions to engage students in a critical thinking process, the participants’ critical thinking process can vary according to the different perspectives and activities implemented in the classroom and songs in university contexts can be used purposefully to activate thinking in the learning process.